Battery and power consuming device
By optimizing the doping amount of Al in the positive electrode active material, the thickness of the ceramic coating, and the electrolyte injection coefficient, a lithium-ion battery with high energy density and high safety performance was prepared, solving the problem of insufficient battery performance in applications such as EVTOL.
Patent Information
- Application Number
- CN202410038464.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-01-10
- Publication Date
- 2026-11-06
- Estimated Expiration
- 2044-01-10
AI Technical Summary
Existing lithium-ion batteries cannot simultaneously meet the requirements of high energy density and high safety performance in applications such as EVTOL.
By optimizing the relationship between the doping amount of Al element in the positive electrode active material, the thickness of the ceramic coating and the electrolyte injection coefficient, the battery is made to satisfy the relationship 1.0≤a*c/1000b^2≤3.7, thus preparing a battery with a separator containing a ceramic coating.
This technology enables batteries to improve thermal safety and stability while maintaining energy density, meeting the needs of electrical devices such as EVTOL.
Smart Images

Figure BDA0004658960400000121
Abstract
Description
Technical Field
[0001] This invention relates to the field of battery technology, and more specifically, to a battery and an electrical device. Background Technology
[0002] In recent years, with the rapid development of battery technology, its application scope has become increasingly wide. For example, lithium-ion batteries are widely used in power tools, electric bicycles, electric motorcycles, electric vehicles, and energy storage power systems such as hydropower, thermal power, wind power, and solar power plants. With the development of modern society and the advancement of technology, automobiles have gradually become the mainstream means of transportation. As the number of cars increases, traffic congestion is also increasing, bringing vertical take-off and landing (VTOL) equipment into focus. The rising oil prices have also made electric vertical take-off and landing (EVTOL) equipment a technological pursuit. Currently, lithium-ion batteries are the best choice for driving EVTOLs.
[0003] As batteries are used more widely, the requirements for their performance are becoming increasingly stringent. For example, due to the unique characteristics of EVTOL, higher demands are placed on the energy density and safety performance of lithium-ion batteries. Therefore, improving the energy density and safety performance of batteries is an urgent issue that needs to be addressed. Summary of the Invention
[0004] In view of this, the present invention aims to at least partially solve one of the technical problems in the related art. To this end, the present invention provides a battery and an electrical device that can improve the energy density and safety performance of the battery.
[0005] To solve the above-mentioned technical problems, this application is implemented as follows:
[0006] According to one aspect of this application, an embodiment of this application provides a battery, which includes a positive electrode, a negative electrode, an electrolyte, and a separator disposed between the positive electrode and the negative electrode.
[0007] The positive electrode sheet includes a positive electrode material layer containing a positive electrode active material, wherein the positive electrode active material contains Al element, and the separator includes a separator substrate and a coating disposed on at least one surface of the separator substrate, wherein the coating includes a ceramic coating;
[0008] The battery meets the following conditions:
[0009] 1.0≤a*c / 1000b 2 ≤3.7,
[0010] Where a is the doping amount of Al element in the positive electrode active material, in ppm;
[0011] b is the electrolyte injection coefficient, in g / Ah;
[0012] c represents the thickness of the ceramic coating, in μm.
[0013] In addition, the battery according to this application may also have the following additional technical features:
[0014] In some of these embodiments, the battery satisfies the following condition: 1.4 ≤ a*c / 1000b 2 ≤2.7.
[0015] In some embodiments, the doping amount 'a' of Al element in the positive electrode active material is 600ppm to 2000ppm; preferably, the doping amount 'a' of Al element in the positive electrode active material is 800ppm to 1500ppm.
[0016] In some embodiments, the electrolyte injection coefficient b is 1.1 g / Ah to 2.1 g / Ah; preferably, the electrolyte injection coefficient b is 1.4 g / Ah to 1.7 g / Ah.
[0017] In some embodiments, the thickness c of the ceramic coating is 1 μm to 7 μm; preferably, the thickness c of the ceramic coating is 3 μm to 5 μm.
[0018] In some embodiments, the positive electrode active material comprises a lithium-containing transition metal oxide, the general chemical formula of which is:
[0019] Li d Ni x Co y Mn z Al f M n O2;
[0020] Wherein, 1.0≤d≤1.2, 0.8≤x<1, 0.01≤y≤0.15, 0.01≤z≤0.15, 0.001≤f≤0.10, 0≤n≤0.05, x+y+z+f+n=1;
[0021] The M includes at least one of Ti, Cr, B, K, Mg, Zn, Sn, Si, P, Mo, Zr, Fe, V, Ba, Sr, Nb, W, or Cu; optionally, the M includes at least one of Ti, Mg, Zn, Nb, Zr, or Sr.
[0022] In some embodiments, the ceramic particles in the ceramic coating include at least one of alumina, silicon oxide, calcium oxide, titanium oxide, magnesium oxide, boron nitride, zinc oxide, chromium oxide, barium oxide, magnesium hydroxide, or boehmite.
[0023] In some embodiments, the diaphragm substrate includes at least one of polyethylene, polypropylene, poly(p-phenylene terephthalamide), polyethylene terephthalate, polyacrylonitrile, polytetrafluoroethylene, polyamide, or polyimide.
[0024] In some embodiments, the ceramic particles have a particle size of 0.8 μm to 1.2 μm.
[0025] In some embodiments, the electrolyte comprises an organic solvent, which includes at least one of carbonate solvents, carboxylic acid ester solvents, sulfone solvents, ether solvents, or nitrile solvents.
[0026] In some embodiments, the electrolyte further includes an electrolyte salt, which includes at least one of lithium hexafluorophosphate, lithium bis(trifluoromethanesulfonyl)imide, lithium bis(fluorosulfonyl)imide, lithium difluorooxalateborate, or lithium tetrafluoroborate.
[0027] According to another aspect of this application, an embodiment of this application provides an electrical device that includes a battery selected from the foregoing.
[0028] Implementing the technical solution of the present invention has at least the following beneficial effects:
[0029] In the embodiments of this application, the provided battery uses a liquid electrolyte and a positive electrode active material doped with Al (aluminum) element, and a separator containing a ceramic coating. Considering that the doping amount of Al in the positive electrode active material, the thickness of the ceramic coating, and the electrolyte injection coefficient may have a correlation with the energy density and safety performance of the battery, extensive research has been conducted to quantify battery cells such as lithium-ion cells. Important empirical formulas related to battery cell design have been summarized and proposed. That is, when the battery satisfies the relationship 1.0≤a*c / 1000b^2≤3.7, the coordination between the doping amount of Al in the positive electrode active material, the thickness of the ceramic coating, and the electrolyte injection coefficient can be balanced. This can improve the safety performance while ensuring the battery energy density, providing a battery with high energy density and high safety performance that can meet the requirements of electrical devices such as EVTOL.
[0030] Additional aspects and advantages of this application will be set forth in part in the description which follows, and in part will be obvious from the description, or may be learned by practice of the invention. Detailed Implementation
[0031] The present application will be further described below with reference to specific embodiments. It should be understood that these embodiments are for illustrative purposes only and are not intended to limit the scope of the present application.
[0032] The endpoints and any values of the ranges disclosed herein are not limited to the precise ranges or values, and these ranges or values should be understood to include values close to these ranges or values. For numerical ranges, the endpoint values of the various ranges, the endpoint values of the various ranges or individual point values, and individual point values can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed herein.
[0033] Unless otherwise specified, the terms "comprising" and "including" as used in this application can be open-ended or closed-ended. For example, "comprising" and "including" can mean that other components not listed may also be included, or that only the listed components may be included.
[0034] Given the increasingly stringent requirements placed on the energy density and safety performance of existing electrical devices' power systems, such as batteries, there is a need to optimize these aspects. This application provides a battery, also known as a rechargeable battery or accumulator, which is a battery that can be recharged after discharge to activate its active materials and continue to be used. The battery includes a positive electrode, a negative electrode, an electrolyte, and a separator. The positive electrode includes a positive current collector and a positive electrode material layer, and the positive active material in the positive electrode contains Al. The separator includes a ceramic coating.
[0035] This application investigates the relationship between Al doping amount in the positive electrode active material, ceramic coating thickness, and electrolyte injection coefficient to optimize the entire battery system, thereby improving the battery's energy density and safety performance. This allows the battery to maintain high safety performance while achieving excellent energy density. In other words, by quantifying various performance aspects of high energy density and high safety, a high-energy-density, high-safety battery can be provided, meeting the needs of electrical devices such as EVTOL cells. Specific technical solutions are described below.
[0036] In some embodiments, this application provides a battery, which includes a positive electrode, a negative electrode, an electrolyte, and a separator disposed between the positive electrode and the negative electrode.
[0037] The positive electrode sheet includes a positive current collector and a positive electrode material layer disposed on at least one side of the positive current collector. The positive electrode material layer includes a positive electrode active material containing Al element.
[0038] The separator includes a separator substrate and a coating disposed on at least one surface of the separator substrate, the coating including a ceramic coating;
[0039] The battery must meet the following condition: 1.0 ≤ a*c / 1000b 2 ≤3.7,
[0040] Where a is the doping amount of Al element in the positive electrode active material, in ppm;
[0041] b is the electrolyte injection coefficient, in g / Ah;
[0042] c represents the thickness of the ceramic coating, in μm.
[0043] This invention can simultaneously improve battery energy density and safety performance for the following reasons:
[0044] The doping amount of Al in the positive electrode active material has a significant impact on the energy density and thermal safety stability of the battery cell. On the one hand, increasing the Al doping amount can improve the structural stability of the positive electrode active material. That is, Al can stabilize the positive electrode structure and increase the oxygen release temperature of the positive electrode material, thus improving the thermal safety stability of the battery cell. On the other hand, Al plays a stabilizing role in the positive electrode material and does not undergo valence state changes during charging and discharging. Therefore, doped Al does not contribute to capacity. Al doping leads to a decrease in the proportion of Ni, Co, and Mn in the positive electrode active material, reducing the specific capacity of the positive electrode material. In other words, the specific capacity of the material decreases with increasing Al doping amount, and excessive Al doping will reduce the energy density of the battery cell. Therefore, it is necessary to keep the Al doping amount in the positive electrode active material within a certain range to better improve thermal safety stability while ensuring battery energy density.
[0045] The electrolyte injection coefficient also has a certain impact on the energy density and thermal safety stability of the battery cell. Increasing the electrolyte injection coefficient, i.e., increasing the electrolyte volume in the cell, leads to a decrease in energy density due to the increased cell weight; conversely, decreasing the electrolyte injection coefficient increases energy density due to the reduced cell weight. However, if the electrolyte volume is too low, insufficient wetting of the electrode surfaces affects the cell interface, making it prone to lithium plating and black spots, thus impacting the specific capacity of the positive electrode material and ultimately reducing the cell's energy density. Simultaneously, the cell's safety performance is also closely related to the electrolyte volume. Lowering the electrolyte volume reduces surface wetting; in the event of a valve opening, electrolyte evaporation can disrupt the ion channels between the positive and negative electrodes, increasing the thermal runaway temperature but decreasing the maximum temperature after thermal runaway. Therefore, it is necessary to control the electrolyte injection coefficient within an appropriate range to improve thermal safety stability while maintaining battery energy density.
[0046] The thickness of the ceramic coating on the separator surface has a significant impact on the energy density and thermal safety performance of the battery cell. Increasing the thickness of the ceramic coating on the separator surface can increase the weight of the separator, reduce the number of electrode layers, and thus increase the proportion of auxiliary materials in the battery cell, thereby reducing the energy density of the battery cell. Conversely, reducing the thickness of the ceramic coating on the separator surface can increase the energy density of the battery cell. On the other hand, increasing the thickness of the ceramic coating on the separator surface can increase the thermal shrinkage temperature of the separator and enhance its mechanical strength at high temperatures, thereby increasing the thermal runaway temperature of the battery cell and improving the thermal safety stability of the battery.
[0047] Therefore, for batteries, the amount of Al doping in the positive electrode active material, the thickness of the ceramic coating, and the electrolyte injection coefficient all have a significant impact on the battery's energy density and thermal safety stability. Furthermore, it is difficult for batteries such as lithium-ion batteries to simultaneously achieve the highest energy density and the highest thermal stability. The inventors of this application have achieved superior thermal safety stability and energy density by optimizing the relationship between the amount of Al doping in the positive electrode active material, the electrolyte injection volume, and the thickness of the ceramic coating on the separator surface. That is, when the battery meets the following condition: 1.0 ≤ a*c / 1000b 2 When the value is ≤3.7, it can achieve relatively excellent thermal safety stability and energy density.
[0048] Based on the relationship provided by this invention, when designing battery cells, using the above empirical formula as a guide can avoid a large number of DOE experiments, save battery R&D time and costs, and enable the designed battery to have both excellent energy density and high thermal safety stability.
[0049] When the value of a*c / 1000b^2 is too low, such as less than 1.0, the thermal runaway temperature will be reduced. For example, if the stability of the positive electrode active material is poor, it will lead to a lower thermal runaway temperature; or if the ceramic coating is too thin, the coating will have low mechanical strength at high temperatures, causing shrinkage and damage, resulting in a short circuit between the positive and negative electrodes and generating heat, thus making the thermal runaway temperature lower.
[0050] When the value of a*c / 1000b^2 is too high, such as greater than 3.7, it will reduce the energy density of the battery. For example, it will affect the specific capacity of the material, resulting in a decrease in the energy density of the battery; or the ceramic coating is too thick, occupying too much space in the thickness direction, which will also reduce the energy density of the cell.
[0051] The aforementioned batteries can be, for example, lithium-ion batteries, sodium-ion batteries, magnesium-ion batteries, potassium-ion batteries, etc., but are not limited to these. In this invention, the batteries can be manufactured into batteries with different structures as needed, without any particular limitation. As examples, the battery structures of this application include, but are not limited to, pouch batteries, square hard-shell batteries, or cylindrical hard-shell batteries. That is, the battery can be cylindrical, flat, cuboid, or other shapes.
[0052] It should be noted that, in the specific implementation, lithium-ion batteries are used as an example to explain this application, but the batteries in this application are not limited to lithium-ion batteries.
[0053] Through in-depth research, the inventors have discovered that, in addition to meeting the above design conditions, the battery of this application can further improve its energy density, thermal safety stability, etc., if it can also optionally meet one or more of the following conditions.
[0054] In some embodiments, the battery satisfies 1.4 ≤ a*c / 1000b 2 ≤2.7.
[0055] As an example, the value of a*c / 1000b^2 can be 1.0, 1.07, 1.09, 1.3, 1.4, 1.5, 1.6, 1.7, 1.8, 2, 2.1, 2.2, 2.4, 2.5, 2.6, 2.7, 2.8, 3.0, 3.1, 3.3, 3.5, 3.7, or any point value within the range of pairwise combinations.
[0056] By ensuring that the battery meets the above conditions, while maintaining a high energy density, the thermal safety stability of the battery can be further improved, which means improving the battery's safety performance.
[0057] In some embodiments, the Al doping amount 'a' in the positive electrode active material is 600ppm to 2000ppm; in some embodiments, the Al doping amount 'a' in the positive electrode active material is 800ppm to 1500ppm. As an example, 'a' can be any value within the range of 600ppm, 700ppm, 800ppm, 900ppm, 1000ppm, 1200ppm, 1400ppm, 1500ppm, 1600ppm, 1800ppm, 2000ppm, or any combination thereof.
[0058] When the Al doping amount in the positive electrode active material is too low, it will affect the overall structural or surface stability of the positive electrode active material, failing to effectively suppress the reaction and heat generation between the positive electrode material and the electrolyte at high temperatures, reducing the stability of the positive electrode at high temperatures, and failing to effectively reduce heat generation, thus leading to a decrease in the thermal runaway temperature. When the Al doping amount in the positive electrode active material is too high, it will affect the specific capacity of the positive electrode active material, leading to a decrease in the energy density of the battery cell. Therefore, in this embodiment of the invention, the mass percentage 'a' of Al in the positive electrode active material is preferably 600 ppm to 2000 ppm. When the Al doping amount meets the above-mentioned range, it can effectively ensure the battery energy density and high thermal runaway temperature.
[0059] In this embodiment, the method for testing the Al doping amount in the positive electrode active material can be as follows:
[0060] (1) Weigh 0.1-0.3g of positive electrode active material and add 10ml of hydrochloric acid solution (hydrochloric acid to water volume ratio is 1:1).
[0061] (2) Digest at 230°C for 30 minutes on a heating plate.
[0062] (3) The solution after decomposition (Al element dissolved in the solution) was tested using ICP (inductively coupled plasma atomic emission spectrometer).
[0063] In some embodiments, the electrolyte injection coefficient b is 1.1 g / Ah to 2.1 g / Ah. Preferably, in some embodiments, the electrolyte injection coefficient b is 1.4 g / Ah to 1.7 g / Ah. As an example, b can be 1.1 g / Ah, 1.2 g / Ah, 1.3 g / Ah, 1.4 g / Ah, 1.5 g / Ah, 1.6 g / Ah, 1.7 g / Ah, 1.1 g / Ah, 1.8 g / Ah, 1.9 g / Ah, 2.0 g / Ah, 2.1 g / Ah, or any value within a combination of any two values.
[0064] When the electrolyte injection coefficient is too low, the electrode surface is not sufficiently wetted, affecting the cell interface and leading to black spot lithium plating. This affects the specific capacity of the cathode material, resulting in a decrease in the cell's energy density. When the electrolyte injection coefficient is too high, it increases the wetting of the cell surface, lowers the cell's thermal runaway temperature, and increases the maximum temperature after thermal runaway. Therefore, in this embodiment of the invention, the electrolyte injection coefficient b is preferably 1.1 g / Ah to 2.1 g / Ah. When the electrolyte injection coefficient meets the above-mentioned value range, it can effectively ensure the battery's energy density and high thermal runaway temperature.
[0065] In some embodiments, the thickness c of the ceramic coating is 1 μm to 7 μm; in some embodiments, the thickness c of the ceramic coating is 3 μm to 5 μm. As an example, c can be any value within the range of 1 μm, 2 μm, 3 μm, 4 μm, 5 μm, 6 μm, 7 μm, or any combination thereof.
[0066] When the thickness of the ceramic coating is too low, it reduces the mechanical strength of the coating at high temperatures, causing shrinkage and breakage that leads to short circuits and heat generation between the positive and negative electrodes, resulting in a lower thermal runaway temperature and reduced thermal safety stability. When the thickness of the ceramic coating is too high, it encroaches on the space in the thickness direction of the battery cell, reducing the proportion of active material and thus lowering the energy density. Therefore, in this embodiment of the invention, the thickness c of the ceramic coating is preferably 1μm to 7μm. When the thickness of the ceramic coating is within the above-mentioned range, it can effectively ensure the battery's energy density and high thermal runaway temperature.
[0067] In this embodiment, the positive electrode includes a positive current collector and a positive electrode material layer disposed on at least one side or at least one surface of the positive current collector. The phrase "a positive electrode material layer disposed on at least one side or at least one surface of the positive current collector" means that the positive electrode material layer can be disposed on one surface of the positive current collector along its thickness direction, or on two surfaces of the positive current collector along its thickness direction. Here, "surface" can refer to the entire area of the positive current collector or only a portion of it; this application does not impose any particular limitation, as long as the purpose of this application is achieved.
[0068] As an example, the positive electrode current collector has two surfaces opposite each other in its own thickness direction, and the positive electrode material layer is disposed on the two opposite surfaces of the positive electrode current collector. It can be understood that the positive electrode material layer can also be stacked on either of the two surfaces of the positive electrode current collector.
[0069] In some embodiments, the positive current collector may be a metal foil or a composite current collector.
[0070] This application does not impose any particular limitation on the positive electrode current collector; any positive electrode current collector well-known to those skilled in the art can be used, as long as it achieves the purpose of this application. As an example, the metal foil can be aluminum foil, aluminum alloy foil, carbon-coated aluminum foil, or nickel mesh, etc. The composite current collector may include a polymer material base layer (such as polypropylene, polyethylene terephthalate, polybutylene terephthalate, polystyrene, polyethylene, etc.) and a metal material layer formed on at least one surface of the polymer material base layer; the metal material layer may include at least one of aluminum, aluminum alloy, nickel, nickel alloy, titanium, titanium alloy, silver, and silver alloy. In this embodiment, the positive electrode current collector is preferably aluminum foil, carbon-coated aluminum foil, or nickel mesh.
[0071] This embodiment does not have any particular limitation on the thickness of the positive current collector; the thickness of the positive current collector can be a conventional thickness in the art.
[0072] The positive electrode active material in the positive electrode material layer of this application may include any material known in the art. For example, the positive electrode active material may be selected from lithium-ion nickel-cobalt-manganese oxides, such as ternary cathode materials doped with Al, but is not limited to these. Other lithium-containing transition metal oxides doped with aluminum may also be used.
[0073] Optionally, the positive electrode active material can be a high-nickel positive electrode active material doped with aluminum. For example, the positive electrode active material can be a high-nickel ternary material doped with aluminum.
[0074] In some embodiments, the positive electrode active material comprises a lithium-containing transition metal oxide, the general chemical formula of which is:
[0075] Li d Ni x Co y Mn z Al f M n O2;
[0076] Wherein, 1.0≤d≤1.2, 0.8≤x<1, 0.01≤y≤0.15, 0.01≤z≤0.15, 0.001≤f≤0.10, 0≤n≤0.05, x+y+z+f+n=1;
[0077] M includes at least one of Ti, Cr, B, K, Mg, Zn, Sn, Si, P, Mo, Zr, Fe, V, Ba, Sr, Nb, W, or Cu;
[0078] Preferably, M includes at least one of Ti, Mg, Zn, Nb, Zr, or Sr.
[0079] Preferably, in some embodiments, f satisfies: f = a / 1000000 / 27 * molar mass of the ternary material. By optimizing the range of values for f, the doping amount of Al can be optimized, that is, the doping amount a of Al in the positive electrode active material can be kept within the required range.
[0080] However, this application is not limited to these materials. Other traditional materials that can be used as positive electrode active materials for batteries can also be used, as long as they contain aluminum, without limiting the purpose of this application. These positive electrode active materials can be used alone or in combination of two or more.
[0081] In some embodiments, the mass of the positive electrode active material is 94% to 98% of the mass of the positive electrode material layer, and more particularly, it can be 95% to 98%.
[0082] In some embodiments, the positive electrode material layer further includes a binder and optionally a conductive agent, the binder improving the bonding between the positive electrode active material particles and also improving the bonding between the positive electrode active material and the positive electrode current collector.
[0083] The conductive agent in the aforementioned positive electrode material layer can be any conductive agent well known to those skilled in the art, and there are no special limitations. As an example, the conductive agent includes one or more of conductive graphite, conductive carbon black, conductive carbon fiber, carbon nanotubes, or graphene.
[0084] In some embodiments, the mass of the conductive agent is 0.5% to 2% of the mass of the positive electrode material layer, and more particularly, it can be 1% to 1.8%.
[0085] The binder in the aforementioned positive electrode material layer can be any binder well known to those skilled in the art, and there are no particular limitations. For example, the binder includes one or more of the following: chitosan, xanthan gum, gellan gum, gum arabic, polyacrylonitrile, polyvinylidene fluoride, polyvinyl alcohol, carboxymethyl cellulose, lithium carboxymethyl cellulose, sodium carboxymethyl cellulose, polymethacrylamide, polyacrylic acid, lithium polyacrylate, sodium polyacrylate, polyacrylamide, styrene-butadiene rubber, sodium alginate, polyethylene glycol, guar gum, guar gum polymers, or guar gum copolymers.
[0086] In some embodiments, the mass of the binder is 0.8% to 2% of the mass of the cathode material layer, and more particularly, it can be 1.2% to 1.8%.
[0087] The positive electrode sheet can be prepared by methods known in the art. For example, the positive electrode sheet can be obtained by mixing a positive electrode active material, a conductive agent, and a binder in a solvent to prepare an active material composition, and then coating the active material composition onto a positive electrode current collector. In some embodiments, the solvent may include, but is not limited to, N-methylpyrrolidone, etc.
[0088] In some embodiments, the negative electrode sheet includes a negative current collector and a negative electrode film layer disposed on at least one surface of the negative current collector. The phrase "a negative electrode film layer disposed on at least one surface of the negative current collector" means that the negative electrode film layer can be disposed on one surface of the negative current collector along its thickness direction, or on two surfaces of the negative current collector along its thickness direction. Here, "surface" can refer to the entire area of the negative current collector or only a portion of it; this application does not impose any particular limitation, as long as the purpose of this application is achieved.
[0089] As an example, the negative electrode current collector has two surfaces opposite each other in its own thickness direction, and the negative electrode film layer is disposed on the two opposite surfaces of the negative electrode current collector. It can be understood that the negative electrode film layer can also be stacked on either of the two surfaces of the negative electrode current collector.
[0090] This application does not impose any particular limitation on the negative electrode current collector; any negative electrode current collector well-known to those skilled in the art can be used, as long as it achieves the purpose of this application. In some embodiments, the negative electrode current collector may be a metal foil or a composite current collector. The metal foil includes copper foil, copper alloy foil, nickel foil, titanium foil, etc. The composite current collector may include a polymer material base layer and a metal material layer formed on at least one surface of the polymer material base layer. In this embodiment, the negative electrode current collector is preferably copper foil.
[0091] In some embodiments, the thickness of the negative electrode current collector is 3μm to 50μm, preferably 5μm to 30μm, more preferably 5μm to 20μm, and most preferably 4.5μm to 8μm.
[0092] In some embodiments, the negative electrode film layer includes a negative electrode active material, which may be a negative electrode active material known in the art for use in batteries. This application does not have any particular limitation on the type of negative electrode active material, as long as it can achieve the purpose of this application.
[0093] As an example, the negative electrode active material includes one or more of silicon-based materials, graphite, soft carbon, hard carbon, carbon fiber, and mesophase carbon microspheres.
[0094] However, this application is not limited to these materials, and other conventional materials that can be used as negative electrode active materials in batteries may also be used. These negative electrode active materials may be used alone or in combination of two or more.
[0095] In some embodiments, the mass of the negative electrode active material is 94% to 98% of the mass of the negative electrode film, and more particularly, it can be 95% to 97%.
[0096] In some embodiments, the negative electrode film layer further includes at least one of a conductive agent, a thickener, and a binder. This application does not impose any particular limitation on the types of conductive agents, thickeners, and binders in the negative electrode film layer, as long as they achieve the purpose of this application.
[0097] As an example, the conductive agent in the negative electrode film layer may be selected from one or more of conductive graphite, conductive carbon black, conductive carbon fiber, carbon nanotubes, and graphene. The binder in the negative electrode film layer may be selected from one or more of chitosan, xanthan gum, gellan gum, gum arabic, polyacrylonitrile, polyvinylidene fluoride, polyvinyl alcohol, carboxymethyl cellulose, lithium carboxymethyl cellulose, sodium carboxymethyl cellulose, polymethacrylamide, polyacrylic acid, lithium polyacrylate, sodium polyacrylate, polyacrylamide, styrene-butadiene rubber, sodium alginate, polyethylene glycol, guar gum, guar gum polymers, and guar gum copolymers. The thickener may be sodium carboxymethyl cellulose (CMC-Na).
[0098] In some embodiments, the mass of the conductive agent is 0.2% to 10% of the mass of the negative electrode film, preferably 0.5% to 8%, more preferably 0.8% to 5%, and most preferably 1% to 3%.
[0099] In some embodiments, the mass of the binder is 0.3% to 10% of the mass of the negative electrode film, preferably 0.5% to 8%, more preferably 1% to 5%, and most preferably 2% to 4%.
[0100] In this invention, there are no special limitations on the material of the separator substrate in the separator membrane; any separator material well known to those skilled in the art can be used. As an example, in some embodiments, the separator substrate includes at least one of polyethylene, polypropylene, poly(p-phenylene terephthalamide), polyethylene terephthalate, polyacrylonitrile, polytetrafluoroethylene, polyamide, or polyimide. In this embodiment, the separator substrate is preferably polyethylene, polypropylene, or a mixture of polyethylene and polypropylene.
[0101] The aforementioned "separator membrane includes a separator substrate and a coating disposed on at least one surface of the separator substrate" means that the coating may be disposed on one surface of the separator substrate along its own thickness direction, or on two surfaces of the separator substrate along its own thickness direction. Here, "surface" may be the entire area of the separator substrate or a part of the separator substrate. This application does not have any particular limitation, as long as the purpose of this application can be achieved.
[0102] As an example, the diaphragm substrate has two surfaces opposite each other in its own thickness direction, and the coating is disposed on the two opposite surfaces of the diaphragm substrate. It is understood that the coating may also be laminated on either of the two surfaces of the diaphragm substrate.
[0103] The coating described above includes a ceramic coating; for example, the coating may consist only of a ceramic coating. Of course, in other embodiments, the coating may also include other types of coatings, such as an adhesive layer, etc., and the present invention does not impose any particular limitations on this.
[0104] In some embodiments, the ceramic particles in the ceramic coating include at least one of alumina, titanium dioxide, zirconium oxide, barium titanate, yttrium-doped zirconium oxide, gadolinium-doped cerium oxide, lithium aluminate, lithium lanthanum titanate, lithium titanium aluminum phosphate, lithium lanthanum zirconate, or lithium zirconium lanthanum tantalate.
[0105] However, this application is not limited to these ceramic materials. Other conventional materials that can be used as the separator coating can also be used, such as silicon oxide, calcium oxide, titanium oxide, magnesium oxide, boron nitride, zinc oxide, chromium oxide, barium oxide, magnesium hydroxide, boehmite, etc., as long as they do not limit the purpose of this application. These ceramic materials can be used alone or in combination of two or more.
[0106] In some embodiments, the particle size of the ceramic particles is 0.8 μm to 1.2 μm. In some embodiments, the particle size of the ceramic particles is 0.9 μm to 1.1 μm.
[0107] In some embodiments, the thickness of the diaphragm substrate is 5 μm to 15 μm. In some embodiments, the thickness of the diaphragm substrate is 6 μm to 13 μm.
[0108] According to the present invention, the electrolyte can be any electrolyte well known to those skilled in the art, and there are no special limitations. As an example, the electrolyte in the present invention includes lithium salt and organic solvent, wherein the types of lithium salt and organic solvent are not specifically limited and can be selected according to actual needs.
[0109] Optionally, the lithium salt preferably includes one or more of lithium hexafluorophosphate, lithium bis(fluorosulfonyl)imide, lithium bis(trifluoromethanesulfonyl)imide, lithium tetrafluoroborate, lithium dioxalate borate, lithium trifluoromethanesulfonate, lithium difluoroborate oxalate, lithium difluorophosphate, lithium 4,5-dicyano-2-trifluoromethylimidazolium, lithium difluorodioxalate phosphate, and lithium tetrafluorooxalate phosphate.
[0110] Optionally, the organic solvent includes at least one of carbonate solvents, carboxylic acid ester solvents, sulfone solvents, ether solvents, or nitrile solvents. Specifically, the organic solvent preferably includes one or more of 1,2-dimethoxypropane, dimethoxymethane, ethylene glycol dimethyl ether, tetrahydrofuran, 2-methyltetrahydrofuran, propylene carbonate, ethylene carbonate, dimethyl carbonate, diethyl carbonate, methyl ethyl carbonate, methyl acetate, methyl propionate, ethyl propionate, propyl acetate, and propyl propionate.
[0111] Optionally, the concentration of lithium salt in the electrolyte is preferably 0.1–6 mol / L, more preferably 0.5–4 mol / L, even more preferably 1–3 mol / L, and most preferably 1–2 mol / L.
[0112] In this embodiment of the invention, the battery can be selected as either wound or stacked, and the manufacturing method is not limited.
[0113] This invention achieves excellent energy density and maintains a high thermal runaway temperature by rationally combining the doping amount of Al element in the positive electrode active material, the electrolyte injection coefficient, and the thickness of the ceramic coating, thus enabling the battery cell to meet the EVTOL requirements in terms of energy density performance and safety.
[0114] In some embodiments, this application provides an electrical device that includes a battery selected from those described above.
[0115] Optional, the electrical device is EVTOL.
[0116] It should be understood that the battery provided by this invention can be used in EVTOL, but is not limited thereto. Other electrical devices with the same or similar needs can also use the battery provided by this invention. For example, electrical devices can also be mobile phones, tablets, laptops, e-book players, electric toys, power tools, lighting fixtures, vehicles such as electric vehicles, electric cars, electric bicycles, electric trucks, etc., ships, other aircraft, energy storage systems, and other electrical devices.
[0117] To further illustrate the present invention, the battery of the present invention will be described in detail below with reference to the embodiments. All reagents used in the following embodiments are commercially available.
[0118] Example 1
[0119] 1. Preparation of positive electrode sheet
[0120] Lithium nickel cobalt manganese oxide cathode active materials containing Al element doping, such as LiNi 0.798 Co 0.099 Mn 0.099 Al 0.004 O2, a composition of conductive carbon black (SP) and carbon nanotubes, and a binder of polyvinylidene fluoride (PVDF) are mixed in a mass ratio of 98.2:0.8:1. Then N-methylpyrrolidone (NMP) is added, and the mixture is stirred and mixed uniformly to form a stable positive electrode slurry. The positive electrode slurry is uniformly coated on the positive electrode current collector aluminum foil, and then dried, cold-pressed, and slit to obtain the positive electrode sheet.
[0121] The doping amount of Al element 'a' in the positive electrode active material is 1200 ppm.
[0122] 2. Preparation of negative electrode sheet
[0123] The negative electrode active materials graphite and silicon carbide, conductive agents SP and CNT, and binders styrene-butadiene rubber PAA and SBR are mixed in a ratio of graphite:silicon carbide:SP:CNT:PAA:SBR = 76.2:19:1.4:0.1:1.1:2.2. Deionized water is added and the mixture is stirred to form a uniform and stable negative electrode slurry. The negative electrode slurry is uniformly coated onto the copper foil on the negative electrode current collector. After drying, cold pressing, and slitting, the negative electrode sheet is obtained.
[0124] 3. Preparation of electrolyte
[0125] In a glove box filled with inert gas, ethylene carbonate, methyl ethyl carbonate, and diethyl carbonate were mixed in a mass ratio of 1:1:1. Then, lithium salt LiPF6 was dissolved in an organic solvent with a concentration of 1.2 mol / L to obtain the electrolyte.
[0126] 4. Separating membrane
[0127] Polypropylene film is selected as the substrate for the isolation membrane, and Al2O3 ceramic is coated on one side to form a ceramic coating.
[0128] The thickness c of the ceramic coating is 4 μm.
[0129] 5. Preparation of lithium-ion batteries
[0130] The positive electrode, separator, and negative electrode are arranged and assembled in sequence. There are two assembly methods: winding and stacking.
[0131] The electrolyte is injected into the dry cell, and after formation and aging, a lithium-ion battery is obtained.
[0132] The electrolyte injection coefficient b is 1.5 g / Ah.
[0133] Example 2-10
[0134] The lithium-ion batteries in Examples 2-10 were all prepared according to the preparation method of Example 1 above. The only difference was the setting of the doping amount of Al element a in the positive electrode active material, the electrolyte injection coefficient b, and the thickness c of the ceramic coating. The specific differences are shown in Table 1.
[0135] Comparative Examples 1-9
[0136] The lithium-ion batteries in Comparative Examples 1-9 were all prepared according to the preparation method of Example 1 above. The only differences were the doping amount of Al element a in the positive electrode active material, the electrolyte injection coefficient b, and the thickness c of the ceramic coating. The specific differences are shown in Table 1.
[0137] Performance testing
[0138] The lithium-ion batteries prepared in the above embodiments and comparative examples were subjected to energy density and thermal safety stability tests (performance calculations were based on model 2614897).
[0139] Test conditions: Energy density = 1 / 3C discharge energy / cell weight; Energy density was tested using an electrochemical charge-discharge cabinet at 25℃ and 1 / 3C.
[0140] Safety performance is characterized by thermal runaway temperature, the highest temperature of the cell after thermal runaway. The test procedure includes:
[0141] (1) Fully charge the battery cell at 25°C, 1C CC to 4.25V and CV to 0.05C, and let it stand for 30 minutes; (2) Increase the temperature to 130°C at room temperature at 5°C / min and hold for 30 minutes; (3) Stop the constant temperature and continue to observe for 1 hour; (4) If it does not fail, increase the temperature to 130°C again at 5°C / min and hold for 30 minutes; (5) If it does not fail, continue to heat to 135°C and hold for 30 minutes; (6) Heat at a gradient of 5°C / min and hold for 30 minutes, ... until it fails.
[0142] The battery thermal runaway temperature is the temperature of the battery cell at the time of thermal runaway. The highest temperature after battery runaway is the highest temperature of the battery cell after thermal runaway, when the battery burns or explodes. The temperature sensing point of the battery cell is located on the top cover between the explosion-proof valve and the electrolyte injection hole.
[0143] The test results are shown in Table 1 below.
[0144] Table 1. Lithium-ion batteries prepared in each embodiment and comparative example, and test results.
[0145]
[0146] The energy density in the embodiment is calculated based on model 2614897 (a battery model).
[0147] Table 1 shows that Comparative Examples 1 / 2, 1, 2-5, and 3 compared the effects of aluminum doping in the cathode material on the safety performance and energy density of the battery cell. With increasing aluminum doping, the energy density of the battery cell gradually decreases, while the thermal runaway temperature gradually increases, and the maximum temperature after thermal runaway gradually decreases. The better the battery cell's safety performance, the better. Comparative Example 1 / 2 does not satisfy 1.0 < a*c / 1000b. 2 <3.7, the energy density of the battery cell is slightly higher, but the thermal failure temperature is not higher than 130℃, which does not meet the national standard requirements for thermal runaway. Comparative Example 3 also does not meet 1.0 < a*c / 1000b. 2 <3.7, excessive Al doping did not increase the battery thermal failure temperature compared to Example 5. Further increasing the doping amount did not improve safety performance, but it did lead to a continuous decrease in energy density. Examples 2 / 5 satisfy 1.0 ≤ a*c / 1000b. 2 ≤3.7, both energy density and safety performance are within a suitable range; Examples 3 / 4 satisfy the preferred 1.4≤a*c / 1000b 2 With a strength of ≤2.7, the battery cell performance is more balanced.
[0148] Comparative Examples 1 / 4-6 and Examples 6-8 compared the effects of the electrolyte injection coefficient on safety performance and energy density. In Comparative Example 3 / 4, the electrolyte injection coefficient was too low, failing to provide sufficient lithium-ion channels, leading to increased cell polarization and thus affecting the cell's energy density. In Comparative Example 5, the electrolyte injection coefficient was too high, reducing the cell's energy density, and the excessive electrolyte caused the cell's maximum temperature after thermal runaway to rise, also reducing safety performance. Comparative Examples 3-5 did not meet the requirement of 1.0 < a*c / 1000b. 2 <3.7, Example 8 satisfies 1.0 ≤ a*c / 1000b 2≤3.7, the energy density and safety performance of the battery cell are improved compared to the previous embodiment. Embodiments 6 / 7 satisfy the preferred 1.4≤a*c / 1000b. 2 ≤2.7, the safety performance and energy density of the battery cell are further improved compared to Example 8.
[0149] The effects of the thickness of the ceramic layer on the diaphragm surface of Comparative Examples 7-9 and Examples 1 / 9 / 10 on the energy density and safety performance of the battery cell were compared. In Comparative Example 7, the ceramic layer on the diaphragm surface was too thin, resulting in extremely poor safety performance, with a thermal runaway temperature of 120°C, lower than the national standard of 130°C. In Comparative Examples 8 / 9, the ceramic layer on the diaphragm surface was too thick, improving the safety performance of the battery cell, but the energy density of the battery cell was too low, and it was also not suitable for the requirements of EVTOL batteries. Examples 1 / 9 / 10 met the preferred requirement of 1.4 ≤ a*c / 1000b. 2 ≤2.7, the energy density and safety performance of the battery cell are within a reasonable range, which is suitable for the requirements of EVTOL battery cells - high energy density and high safety.
[0150] In summary, optimizing the Al doping amount in the cathode, the electrolyte injection amount in the cell, and the ceramic thickness of the separator to satisfy 1.0 ≤ a*c / 1000b 2 With a value ≤3.7, the energy density and thermal stability of the battery cell are comprehensively improved, when 1.4≤a*c / 1000b is satisfied. 2 When the energy density and thermal stability of the battery cell are ≤2.7, the combination is optimal.
[0151] The parts of this invention not described in detail are techniques known to those skilled in the art.
[0152] The basic principles of the present invention have been described above with reference to specific embodiments. However, it should be noted that the advantages, benefits, and effects mentioned in the present invention are merely examples and not limitations, and should not be considered as essential features of each embodiment of the present invention. Furthermore, the specific details disclosed above are for illustrative and facilitative purposes only, and are not limitations. These details do not limit the present invention to the necessity of employing the aforementioned specific details.
[0153] In the detailed description and claims, a list of items connected by the terms "at least one of," "at least one of," "at least one of," or other similar terms may mean any combination of the listed items. For example, if items A and B are listed, then the phrase "at least one of A and B" means only A; only B; or A and B. In another example, if items A, B, and C are listed, then the phrase "at least one of A, B, and C" means only A; or only B; only C; A and B (excluding C); A and C (excluding B); B and C (excluding A); or all of A, B, and C. Item A may contain a single element or multiple elements. Item B may contain a single element or multiple elements. Item C may contain a single element or multiple elements.
[0154] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, and not to limit them; although the present invention has been described in detail with reference to the foregoing embodiments, those skilled in the art should understand that modifications can still be made to the technical solutions described in the foregoing embodiments, or equivalent substitutions can be made to some of the technical features; and these modifications or substitutions do not cause the essence of the corresponding technical solutions to deviate from the spirit and scope of the technical solutions of the embodiments of the present invention.
Claims
1. A battery, characterized in that, It includes a positive electrode, a negative electrode, an electrolyte, and a separator disposed between the positive electrode and the negative electrode; The positive electrode sheet includes a positive electrode material layer containing a positive electrode active material, the positive electrode active material containing Al element, and the separator includes a separator substrate and a coating disposed on at least one surface of the separator substrate, the coating including a ceramic coating, the ceramic coating being coated on one side of the separator substrate; The battery meets the following conditions: 1.0≤a c / 1000b 2 ≤3.7, Wherein, a is the doping amount of Al element in the positive electrode active material, and the doping amount of Al element in the positive electrode active material a is 600ppm to 2000ppm, where ppm is the mass percentage content; b is the electrolyte injection coefficient, in g / Ah; c represents the thickness of the ceramic coating, in μm.
2. The battery according to claim 1, characterized in that, The battery satisfies the following condition: 1.4 ≤ a c / 1000b 2 ≤2.
7.
3. The battery according to claim 1, characterized in that, The doping amount of Al element 'a' in the positive electrode active material is 800ppm to 1500ppm.
4. The battery according to claim 1, characterized in that, The electrolyte injection coefficient b is 1.1 g / Ah to 2.1 g / Ah.
5. The battery according to claim 4, characterized in that, The electrolyte injection coefficient b is 1.4 g / Ah to 1.7 g / Ah.
6. The battery according to claim 1, characterized in that, The thickness c of the ceramic coating is 1μm to 7μm.
7. The battery according to claim 6, characterized in that, The thickness c of the ceramic coating is 3μm to 5μm.
8. The battery according to any one of claims 1 to 7, characterized in that, The positive electrode active material includes a lithium-containing transition metal oxide, and the general chemical formula of the lithium-containing transition metal oxide is: Li d Ni x Co y Mr z Al f M n O2; Wherein, 1.0≤d≤1.2, 0.8≤x<1, 0.01≤y≤0.15, 0.01≤z≤0.15, 0.001≤f≤0.10, 0≤n≤0.05, x+y+z+f+n=1; The M includes at least one of Ti, Cr, B, K, Mg, Zn, Sn, Si, P, Mo, Zr, Fe, V, Ba, Sr, Nb, W, or Cu; optionally, the M includes at least one of Ti, Mg, Zn, Nb, Zr, or Sr.
9. The battery according to any one of claims 1 to 7, characterized in that, The ceramic particles in the ceramic coating include at least one of alumina, silicon oxide, calcium oxide, titanium oxide, magnesium oxide, boron nitride, zinc oxide, chromium oxide, barium oxide, magnesium hydroxide, or boehmite. The diaphragm substrate includes at least one of polyethylene, polypropylene, poly(p-phenylene terephthalamide), polyethylene terephthalate, polyacrylonitrile, polytetrafluoroethylene, polyamide, or polyimide.
10. The battery according to claim 9, characterized in that, The ceramic particles have a particle size of 0.8 μm to 1.2 μm.
11. The battery according to any one of claims 1 to 7, characterized in that, The electrolyte includes an organic solvent, which includes at least one of carbonate solvents, carboxylic acid ester solvents, sulfone solvents, ether solvents, or nitrile solvents. The electrolyte further includes an electrolyte salt, which includes at least one of lithium hexafluorophosphate, lithium bis(trifluoromethanesulfonyl)imide, lithium bis(fluorosulfonyl)imide, lithium difluorooxalateborate, or lithium tetrafluoroborate.
12. An electrical appliance, characterized in that, Includes batteries selected from any one of claims 1 to 11.
Citation Information
Patent Citations
Lithium ion battery
CN117175011A
Lithium ion battery
CN117219856A
